Air-Hole-Assisted Photonic Lanterns - Lijie Hou; Zhiqun Yang; Yaping Liu; Huihui Wang; Bingyi Zhao; Zhanhua Huang; Lin Zhang (Photonics, 2025)
Exploring innovative approaches to enhance the performance of photonic lanterns is greatly valuable. In this paper, we first propose an air-hole-assisted pure silica-based capillary (AHC), featuring a single ring of embedded air holes. As a result, the PL based on the AHC exhibits good performance, successfully exciting LP01, LP11a & LP11b, LP21a & LP21b, LP02, and LP31a & LP21b modes. The average mode loss, mode-dependent loss, and maximum crosstalk are 0.08 dB, 0.04 dB, and −27.2 dB, respectively. In fact, the overall performance of the proposed AHC-based PL is on par with that of the traditional PL. Furthermore, an error analysis is provided to confirm the feasibility of our approach. The AHC-based PLs possess high numerical apertures and are expected to enable high spatial resolution imaging in optical imaging.